HANS KÜNG DAN JOSEPH RATZINGER – DUA PANDANGAN TENTANG YESUS KRISTUS - Georg Ludwig Kirchberger (Jurnal Ledalero, 2021)
Hans Küng and Joseph Ratzinger are two well-known figures whose biography runs parallel to the end of the Second Vatican Council, but since the 1970s they have been sharply separated and since then they have developed into representatives of the two currents of development in the Catholic Church after the Second Vatican Council. In this article the author describes the characteristics of their respective views on Jesus Christ. Hans Küng's views are described according to the concise description in the book “20 Thesen zum Christsein” and his views are summarized under the title Jesus of Nazareth – an exemplary Man. Meanwhile, Joseph Ratzinger's view is taken from his book Jesus of Nazareth, which was published after Ratzinger became Pope Benedict XVI and is summarized under the title Jesus Christ – the Son of God. After describing the two positions, the writer gives a brief response to the two views. Keywords: Hans Küng, Joseph Ratzinger, christology, historical Jesus, critical historical method.